Therapeutic Targeting of Histone Modifications in Adult and Pediatric High-Grade Glioma - Williams, Maria J.; Singleton, Will G. B.; Lowis, Stephen P.; Malik, Karim; Kurian, Kathreena M. (Frontiers in Oncology, 2017)
Recent exciting work partly through The Cancer Genome Atlas (TCGA), has implicated epigenetic mechanisms including histone modifications in the development of both paediatric and adult high grade glioma. Histone lysine methylation has emerged as an important player in regulating gene expression and chromatin function. Lysine (K) 27 (K27) is a critical residue in all seven histone 3 variants and the subject of post-translational histone modifications, as it can be both methylated and acetylated. In paediatric high grade glioma, two critical single point mutations occur in the H3F3A gene encoding the regulatory histone variant H3.3. These mutations occur at lysine (K) 27 (K27M) and glycine (G) 34 (G34R/V), both of which are involved with key regulatory post-transcriptional modifications. These mutations therefore effect gene expression, cell differentiation and telomere maintenance. In recent years, alterations in histone acetylation have provided novel opportunities to explore new pharmacological targeting, with histone deacetylase (HDAC) overexpression reported in high-grade, late-stage proliferative tumours. HDAC inhibitors have shown promising therapeutic potential in many malignancies. This review focuses on the mechanisms propagating paediatric and adult high grade gliomas, as well as summarising the current advances in clinical trials using HDAC inhibitors to combat an aggressive brain tumour.